Peningkatan Keterampilan dan Produktivitas Ekonomis Panti Asuhan Grha Aitam Al Madina - Devyani Diah Wulansari; Emma Savitri; Hayuning Purnama Dewi (Ilin Institute, 2021)
The purpose of this service program is to improve skills and productivity. economical partner. The method used is through mentoring and training programs by academics from the University of Surabaya related to halal certification, analysis of honey content for quality control and improvement of the packaging process to improve the hygiene of honey products. From the results of this community service program, Partners succeeded in obtaining LPPOM MUI halal certificates for Honey products, analysis of water content, metals, ash, microbial contamination, diastase enzymes, and Hydroxymethyl Furfural (HMF) by SNI 8664-2018, and the honey packaging process through the application of appropriate technology to maintain the hygiene and quality of honey.